The bloody white baron : the extraordinary story of the Russian nobleman who became the last Khan of Mongolia - Palmer, James, 1978- (New York : Basic Books, 2009)
Historian James Palmer relates the story of megalomaniac Baron Freiherr Roman Nikolai Maximilian von Ungern-Sternberg, an anti-Bolshevik German Russian reactionary who in 1920 led a lethally effective rabble of cavalrymen in a grand but short lived campaign to unifMongolMongul people while at the same time frightening the Russians and slaughtering everyone he suspected of irreligion or of being a Jew
"Published in 2008 in England by Faber and Faber Unlimited"--T.p. verso
Includes bibliographical references (p. 264-267) and index
Keywords: Ungern-Sternberg, Roman, -- 1885-1921; Generals -- Russia -- Biography; Mongolia -- History, Military -- 20th century; Soviet Union -- History -- Revolution, 1917-1921